Condiciones ambientales ante la caída prematura del fruto del cultivo de naranja (Citrus sinensis) - García Moya, Francisco Antonio (2024)
This bibliographic research document details environmental conditions in the face of the premature fall of the fruit of the orange crop. Highlighting that this crop represents great economic importance for Ecuador, so it is necessary to implement new agronomic techniques that allow minimizing the incidence of premature fall of the orange fruit, with the purpose of improving the productivity and profitability of the crops. of Orange. Environmental conditions are essential factors in the event of premature fruit drop, such as climatic factors, irrigation problems, pests and diseases, seed quality, among others. In order to prevent premature fruit drop, hormones and fruit retention can be used, accompanied by good management of pests and diseases, good agricultural practices that are essential in the face of premature fruit drop. The climate is the most important parameter for choosing the location of an orange grove. Climate primarily determines the success of the orange plant and the quality of the citrus fruit. The climatic factors that influence orange cultivation are temperature and humidity. Taking into account that the temperature should not be low, since it would harm the successful development of the orange crop (Citrus sinensis), the most optimal being 24 °C, therefore, it is necessary to know the edaphoclimatic requirements of the crop.